2010
DOI: 10.1074/jbc.m110.110759
|View full text |Cite
|
Sign up to set email alerts
|

Actinidain-hydrolyzed Type I Collagen Reveals a Crucial Amino Acid Sequence in Fibril Formation

Abstract: We investigated the ability of type I collagen telopeptides to bind neighboring collagen molecules, which is thought to be the initial event in fibrillogenesis. Limited hydrolysis by actinidain protease produced monomeric collagen, which consisted almost entirely of ␣1 and ␣2 chains. As seen with ultrahigh resolution scanning electron microscopy, actinidain-hydrolyzed collagen exhibited unique self-assembly, as if at an intermediate stage, and formed a novel suprastructure characterized by poor fibrillogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…The N-H stretching vibrations of A-CF and P-CF separately appeared at 3423.76 cm −1 and 3324.57 cm −1 , both cases with high peak intensity. There was a relatively weak absorption peak in both A-CF and P-CF at 2957.13 cm −1 and 2934.59 cm −1 , respectively, because of the C-N stretching vibration named Amide B [32]; that is consistent with that recorded by Kunii, et al [33]. Amide I and Amide II bands of collagen were associated with α-helix, β-folding, random crimp coil and superposition.…”
Section: Ftir Spectrasupporting
confidence: 88%
“…The N-H stretching vibrations of A-CF and P-CF separately appeared at 3423.76 cm −1 and 3324.57 cm −1 , both cases with high peak intensity. There was a relatively weak absorption peak in both A-CF and P-CF at 2957.13 cm −1 and 2934.59 cm −1 , respectively, because of the C-N stretching vibration named Amide B [32]; that is consistent with that recorded by Kunii, et al [33]. Amide I and Amide II bands of collagen were associated with α-helix, β-folding, random crimp coil and superposition.…”
Section: Ftir Spectrasupporting
confidence: 88%
“…It has previously been shown that Act d 1 exerted proteolytic activity under simulated gastric and intestinal conditions [16], and the contribution of Act d 1 to the digestion of several food proteins was confirmed in vivo [31]. In our study, an increased intestinal permeability to FITC-dextran was detected in mice which had been given [4][5][6][7][8][9][10] and wide substrate specificity [32], including collagenolytic activity [33]. Apart from contributing to the disruption of tight junctions, the collagenolytic activity of Act d 1 can lead to connective tissue loosening in the lamina propria.…”
Section: Accepted Manuscriptsupporting
confidence: 69%
“…Bovine dermal collagen I (NUTRAGEN) was purchased as a 6.0 mg/ml solution in 0.01 M HCl from Advanced Biomatrix (San Diego, CA). This collagen is isolated from bovine hides by enzymatic digestion with pepsin, Collagen Self-Assembly Kinetics which removes portions from the N-and C-terminal telopeptides containing the lysine groups that are responsible for intermolecular cross-linking in vivo (53). Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) on 4% gels was used to assess the purity and degree of intramolecular cross-linking.…”
Section: Preparation Of Collagen Gelsmentioning
confidence: 99%